Respuesta :
x²+bx=c
x=[-b+√(b²+4c)]/2
2x(x+5)=4
2x²+10x=4
x²+5x=2
x=[-5+√(5²+4*4)]/2
if b=-1/2 and c=-9/2
x= {1/2+√[(1/2)²+4*(-9/2)]}/2
x=[-b+√(b²+4c)]/2
2x(x+5)=4
2x²+10x=4
x²+5x=2
x=[-5+√(5²+4*4)]/2
if b=-1/2 and c=-9/2
x= {1/2+√[(1/2)²+4*(-9/2)]}/2
Answer:
The solutions are:
[tex]x=-5.372\ and\ x=0.372[/tex]
Step-by-step explanation:
The equation is given by:
[tex]2x(x+5)=4[/tex]
on using the distributive property of multiplication in the left hand side of the equation we have:
[tex]2x\times x+2x\times 5=4\\\\i.e.\\\\2x^2+10x=4\\\\i.e.\\\\2x^2+10x-4=0\\\\i.e.\\\\2(x^2+5x-2)=0\\\\i.e.\\\\x^2+5x-2=0[/tex]
Now, we know that the solution of the quadratic equation:
[tex]ax^2+bx+c=0[/tex] is given by:
[tex]x=\dfrac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]
Here we have:
[tex]a=1,\ b=5\ and\ c=-2[/tex]
Hence, the solution is:
[tex]x=\dfrac{-5\pm \sqrt{5^2-4\times 1\times (-2)}}{2\times 1}\\\\i.e.\\\\x=\dfrac{-5\pm \sqrt{25+8}}{2}\\\\i.e.\\\\x=\dfrac{-5\pm \sqrt{33}}{2}\\\\x=\dfrac{-5+\sqrt{33}}{2},\ x=\dfrac{-5-\sqrt{33}}{2}[/tex]
Hence, in decimal for the solution is:
[tex]x=-5.372\ and\ x=0.372[/tex]